Pengaruh Kualitas Pelayanan, Promosi Dan Harga Terhadap Kepuasan Pelanggan Pada Toko Roti Violet Bakery Kota Probolinggo - Dewi, Ivo Yusvita; Hermawan, Dedi Joko; Rahajeng, Yekti (Universitas Panca Marga, 2024)
This research aims to determine to what extent the variables of service quality, promotion and price partially influence customer satisfaction at the Violet Bakery Bakery, Pobolinggo City. The type of research used is quantitative with a causal associative approach. The variables studied were service quality, promotion and price and customer satisfaction at Violet Bakery, Probolinggo City, with a total of 90 respondents. The data analysis method from the research results is a quantitative descriptive method using the SmartPLS program in the form of a convergent validity test, discriminant validity test, reliability test, adjusted R square test, Q square test and hypothesis test. The test results show that 1) service quality (X1) does not have a significant influence on customer satisfaction. 2) promotion (X2) has a significant and negative influence on customer satisfaction. 3) price (X3) has a significant influence on customer satisfaction.